Diversity of Cervical Microbiota in Asymptomatic Chlamydia trachomatis Genital Infection: A Pilot Study - Filardo, Simone; Di Pietro, Marisa; Porpora, Maria G.; Recine, Nadia; Farcomeni, Alessio; Latino, Maria A.; Sessa, Rosa (Frontiers in Cellular and Infection Microbiology, 2017)
Chlamydia trachomatis genital infection continues to be an important public health problem worldwide due to its increasing incidence. C. trachomatis infection can lead to severe sequelae, such as pelvic inflammatory disease, obstructive infertility and preterm birth. Recently, it has been suggested that the cervico-vaginal microbiota may be an important defence factor towards C. trachomatis infection as well as the development of chronic sequelae. Therefore, the investigation of microbial profiles associated to chlamydial infection is of the utmost importance. Here we present a pilot study aiming to characterize, through the metagenomic analysis of sequenced 16s rRNA gene amplicons, the cervical microbiota from reproductive age women positive to C. trachomatis infection. The main finding of our study showed a marked increase in bacterial diversity in asymptomatic C. trachomatis positive women as compared to healthy controls in terms of Shannon’s diversity and Shannon’s evenness (P=0.031 and P=0.026, respectively). More importantly, the cervical microbiota from C. trachomatis positive women and from healthy controls significantly separated into two clusters in the weighted UniFrac analysis (P=0.0027), suggesting that differences between the two groups depended entirely on the relative abundance of bacterial taxa rather than on the types of bacterial taxa present. Furthermore, C. trachomatis positive women showed an overall decrease in Lactobacillus spp. and an increase in anaerobes. These findings are part of an ongoing larger epidemiological study that will evaluate the potential role of distinct bacterial communities of the cervical microbiota in C. trachomatis infection.